Case Report: Virtual surgery and 3D printing in a medication-related osteonecrosis of the jaws (MRONJ) pathological mandibular fracture - Lo Giudice, Giorgio; Calvo, Alessandro; Magaudda, Emanuele; De Ponte, Francesco Saverio; Nastro Siniscalchi, Enrico (Frontiers in Oral Health, 2025)
IntroductionThe use of anatomical models, guides, and surgical templates allows for increased precision of interventions and reduced operative times. Thanks to computer-aided design (CAD) and computer-aided manufacturing (CAM) technologies and rapid prototyping through 3D printing, it is possible to obtain accurate models, which are useful to defining surgical planning in the maxillofacial district.MethodsWe present the case of a patient with a pathological fracture of the mandibular body affected by medication-related osteonecrosis of the jaws (MRONJ) in stage III. Through the manipulation of virtual models obtained from thin-layer Computed Tomography (CT), a virtual surgical intervention of sequestrectomy and debridement of necrotic bone tissue, reduction and containment of the fracture was performed. The resulting mandibular model was used as a template for the preoperative modeling of the titanium reconstruction plate used for fracture containment.ResultsThe intraoperative result and follow-up demonstrated good accuracy of the model with respect to post-operative mandibular dynamics, condylar-fossa position and a reduced surgical time.DiscussionVirtual surgery and 3D-printed prototyping represent a feasible technique in MRONJ patients, allowing increased precision of interventions, reduced risks associated with the operation, and improved operative and recovery times for the patient.